2020
DOI: 10.1002/mabi.201900412
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli Responsive Scaffolds Based on Carboxymethyl Starch and Poly(2‐Dimethylaminoethyl Methacrylate) for Anti‐Inflammatory Drug Delivery

Abstract: The purpose of the study is to obtain multicomponent polyelectrolyte hydrogels with optimal synergistic properties by combining a modified starch with a synthetic one. Thus, new low‐cost and biocompatible semi‐interpenetrating polymer network (semi‐IPN) hydrogels of carboxymethyl starch and poly(2‐dimethylaminoethyl methacrylate) are prepared and investigated. The synthesized hydrogels are studied with respect to the specific characteristics of the gels: swelling kinetics, thermal analysis, viscoelastic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The values of G’ are correlated with the network strength [ 35 , 36 , 37 ]. From Figure 5 and Figure 6 it can be observed that Lys content in the sample influences considerably the gel strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of G’ are correlated with the network strength [ 35 , 36 , 37 ]. From Figure 5 and Figure 6 it can be observed that Lys content in the sample influences considerably the gel strength.…”
Section: Resultsmentioning
confidence: 99%
“…The morphological characterization of hydrogels by SEM analysis provides essential information on the size, shape and distribution of pores in their three-dimensional matrix [38]. The The values of G' are correlated with the network strength [35][36][37]. From Figures 5 and 6 it can be observed that Lys content in the sample influences considerably the gel strength.…”
Section: Sem Microscopymentioning
confidence: 99%
“…Swelling ratios of the porous NGHH from 25 to 51 °C for 24 h were determined gravimetrically ( Figure 7 a). The swelling ratios of these NGHH were not remarkable, which was attributed to the relatively high degree of cross-linking [ 44 ]. An approximately linear drop in swelling ratio occurred from 31 to 37 °C, indicating that the LCST of PNIPAAm is affected by the hydrogen bonding interaction with bovine skin gelatin.…”
Section: Resultsmentioning
confidence: 99%
“…Stimuli-responsive drug delivery system was also developed by Nita et al, [143] who prepared semi-interpenetrating polymer network hydrogels of carboxymethyl starch and poly(2dimethylaminoethyl methacrylate) loaded with ibuprofen. The hydrogels demonstrated pH and temperature responsiveness.…”
Section: Anti-inflammatory Architectures Based On Molecular Complexesmentioning
confidence: 99%
“…Nita et al 2020 [ 143] surface coatings. The researchers covalently immobilized poly(ethyl acrylate-co-methacrylic acid) microgels loaded with human heparin cofactor II-derived peptide KYE28 (KYEITTI-HNLFRKLTHRLFRRNFGYTLR), as well as its poly(ethylene glycol)-conjugated (PEGylated) version, KYE28PEG.…”
mentioning
confidence: 99%